Implementasi Kebijakan Kawasan Perdagangan Bebas/Free Trade Zone (FTZ) Terhadap Masyarakat Bukan Pelaku Usaha di Kota Batam - Cherlyne Baby Florencia; Rasji Rasji (LPPM Universitas Ekasakti Padang, 2023)
A free trade area or also known as a Free Trade Zone (FTZ) is an area that is given exemption from export-import duties, customs duties, Tax, exemption and Sales Tax exemption on Luxury Goods (PPnBM). Based on Government Regulation (PP) Number 46 of 2007 concerning Free Trade Zones and Free Ports in Batam, the city of Batam is designated as a free trade area. This is based on its geographical location, which borders directly with neighboring countries and is on international shipping lines. The policies provided FTZ will certainly have an impact on the people of Batam City, for this reason it is necessary to know the impact of the FTZ policy on the people of Batam City, especially non-business actors. The regulation had various impacts, one of which is from the positive side that makes easier for the people of Batam City to obtain imported goods, but from the negative side it creates difficulties for the people of Batam City who are not business actors in sending goods out of Batam City because must still need to pay Tax. Even though these goods not imported goods or goods for trade, there are no clear provisions regarding the differentiation of goods included in the city of Batam because they are all considered imported goods. For this reason, it’s important for the government to evaluate and reconsider the free trade area policy rules in order to provide policies that can take into account the people of Batam City, especially non-business actors